Plasma Levels of Interleukin 2 (IL-2) Associated with Hearing Loss Evaluation in the Elderly - Fernanda P. Cordeiro; Luciana L.M. Marchiori; Denilson C. Teixeira; Rodrigo A.C. Andraus; Regina Célia Poli-Frederico (Noise and Health)
Context: Presbycusis can be mediated by the effects of inflammatory processes on the auditory system, and these aging biological mechanisms remain poorly studied. Aims: The aim of this study was to determine whether plasma biomarkers are associated with hearing disorders caused by aging in the elderly. Settings and design: Cross-sectional study with 106 participants in the Active Aging Project, 93 (88%) females and 13 (12%) males, with an average age of 70 years. Methods and material: Audiological evaluation was performed with pure tone audiometry and collection of peripheral blood for the measurement of plasma levels of interleukins 2, 4, 6, and 10, tumor necrosis factor-α, and interferon-γ by means of flow cytometry. Statistical analysis used: The SPSS (v.0, SPSS Inc., Chicago, USA) was used for the analysis of the data obtained. For all data analyzed, the significance level adopted was P < 0.05 and 95% confidence interval. Results: There were statistically significant correlations between male and IL-2 (P = 0.031; rs = 0.210), mean II of the right ear (P = 0.004; rs = 0.279), longer in years (P = 0.002; rs = 0.307) and in hours (P = 0.004; rs = 0.281) of noise exposure also in males. Conclusions: In the present study, there was an association between the male gender and higher plasma levels of IL-2, an increase in the average hearing in the right ear, and greater time in years and hours of exposure to noise. There was a predominance of mild sensorineural hearing loss and worsening of hearing related to age, characteristics of presbycusis.